The American Revolution and Christine Desan's New History of Money. Issue 1 (15th August 2016) - David Edwards, Andrew
Abstract : This essay argues that Christine Desan's Making Money: Coin, Currency and the Coming of Capitalism intervenes decisively in debates over the origin of money, while making a fundamental contribution to the legal history of money, the philosophy of money, and the history of capitalism. Desan shows money to be a mode of governance, created by rulers to extend their power, and maintained and managed by their successors. She argues that British politicians reinvented money at the end of the seventeenth century, creating the essential institutional basis for contemporary capitalism. The essay builds on Desan's analysis, showing how the tools she develops to understand the origins and development of British money can help us explain the expansion of capitalism, and the transition to capitalism associated with the American Revolution.